Methodology and Results of Studying the Electrophysical Properties of Plants - Xolmirzayev Ilhom Jummayevich; Eshmurodov Sobir Soat o‘g‘li; Qurbonov Asadbek Yo‘lchi o‘g‘li; Normurodov Ulug‘bek Nurmamat o‘g‘li; Qurbonov Jamshid Sherqo‘zi o‘g‘li (Zien Journals, 2025)
This article discusses methods for studying the electrophysical properties of plants, the importance of bioelectric parameters in determining their physiological state, and experimental results. As a result of the research, it was proven that changes in the capacitance and resistance of plant cell membranes are an important indicator in determining their response to external factors.
Keywords: electrophysiology; membrane potential; plant